Desmoplastic ameloblastoma - Aesha Imran; Sandhya Arun Kumar; Sriram; Satish Muthu Kumar (Wolters Kluwer Medknow Publications, 2016)
The most common odontogenic neoplasm, it accounts for only 1% of all jaw tumors. A variant of Ameloblastoma- Desmoplastic type is known for its unique features and propensity to recur. A 44 year old male patient, report with a swelling in anterior part of lower jaw. Radiograph reveals a mixed radiopaque and radiolucent lesion. Histopathology shows features of Desmoplastic ameloblastoma.